Optimization of Formulation Parameters on Ocular Loteprednol Etabonate Nanosuspension by Media Milling Method - Memon, Abdulganee (International Journal of Pharmaceutical & Biological Archive, 2013)
Optimization of Formulation Parameters on Ocular Loteprednol Etabonate Nanosuspension by Media Milling Method